Driving fibrosis in neuromuscular diseases: Role and regulation of Connective tissue growth factor (CCN2/CTGF) - Daniela L. Rebolledo (Matrix Biology Plus, 2021)
Connective tissue growth factor or cellular communication network 2 (CCN2/CTGF) is a matricellular protein member of the CCN family involved in several crucial biological processes. In skeletal muscle, CCN2/CTGF abundance is elevated in human muscle biopsies and/or animal models for diverse neuromuscular pathologies, including muscular dystrophies, neurodegenerative disorders, muscle denervation, and muscle overuse. In this context, CCN2/CTGF is deeply involved in extracellular matrix (ECM) modulation, acting as a strong pro-fibrotic factor that promotes excessive ECM accumulation. Reducing CCN2/CTGF levels or biological activity in pathological conditions can decrease fibrosis, improve muscle architecture and function. In this work, we summarize information about the role of CCN2/CTGF in fibrosis associated with neuromuscular pathologies and the mechanisms and signaling pathways that regulate their expression in skeletal muscle.